STUDENTS’ PERSPECTIVES ON USING GRAMMAR CHECKERS IN ACADEMIC WRITING - Izzati, Keysa; Noni Agustina; Anindita, Rina (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
Research article writing is essential for academics to disseminate their work and develop their careers. However, writing in a foreign language (FL) is a complex process that entails more than just conveying ideas, involving various procedures to complete the writing task. In an effort to improve students' writing skills, technology-based tools such as grammar checkers have developed rapidly. Thus, this study aims to investigate students' perspectives on the use of grammar checkers in improving their writing skills. The results showed that grammar checkers were generally perceived as practical and useful tools in improving their writing quality, efficiency, and confidence. Most participants felt that grammar checkers helped them in understanding grammar rules and made their writing better. However, despite general satisfaction, some participants still preferred personal judgement in assessing the accuracy of their writing, suggesting that there is still a need to improve the reliability and accuracy of grammar checkers.